Co-pyrolysis of high-density polyethylene and wood mixtures - Erşen, Tuba; Pehlivan, Dursun (My University, 2011)
In the co-pyrolysis of pellets containing HDPE and pine wood in equal proportions, maximum solid yield was obtained at 1°C/min heating rate and for 500°C final temperature under 10 mL/min nitrogen sweeping flow. It was determined that the highest liquid product yield obtained at 5°C/min heating rate and for 700°C final temperature without sweeping.
Yüksek yo?unluklu poli?eti?len-odun karişimlarinin bi?rli?kte pi?roli?zi?
Keywords: Co-pyrolysis; Polyethylene; Wood